Amérindiens de Sinnamary (Guyane) Archéologie en forêt équatoriale - Vacher, Stéphane; Jérémie, Sylvie; Briand, Jérôme (Documents d'archéologie française, 1998)
This work introduces the initial results of research at sites occupied by Native Americans in the Sinnamary basin (1660-220 BP), carried ont at the time of the construction of the Petit Saut dam by Electricité de France in French Guyana. A methodological approach pertaining to the tropical sylvan and riparian milieu is followed by a study of the open-air sites, and a commentary focusing on the phenomenon of terra preta and palaeolithic fires. For the first time a typological tramework and a vocabulary are proposed for reference to lithic senes and polishing-tool sites. This work also includes a study of ceramics using two complementary approaches: determination of place of manufacture based on the Chemical make-up of the pestes employed, and codification of the forms and motifs of the 22,000 objects registered. Following up on the publication devoted to the colonial period in this region (dAf 60), this volume makes a signifiant contribution to the renewal of histonographical work on the Guyana plateau.